Mental health consequences of the COVID-19 pandemic: a narrative Reviews - Danijela Radulović; Svetlana Radević; Srđan Mašić (Биомедицинска истраживања, 2025)
The COVID-19 pandemic has generated a profound psychological impact across diverse populations, exposing long-standing gaps in mental health services and intensifying social inequalities. This narrative Reviews explores the most prevalent mental health conditions associated with the pandemic including depression, anxiety, stress, and post-traumatic stress disorder (PTSD) with emphasis on population-specific vulnerabilities such as sex, age, social status, and chronic illness. Special attention is given to the bidirectional relationship between mental and physical health, the role of social support, and behavioral mediators of psychological distress. The Reviews underscores the need for systemic, multi-level public health responses integrating mental health into pandemic preparedness, healthcare delivery, and social policy. Lessons learned from the COVID-19 crisis offer a unique opportunity to redefine mental well-being as a global public health priority.
Keywords: COVID-19 pandemic; mental health; depression; anxiety; PTSD; risk factors for mental health